LINGVISTIKADA «KONCEPT» TÚSINIGI - Muratbaeva, U.T. (SCIENCE and SOCIETY, 2024)
The article examines the concept of in cognitive linguistics as a unit of linguoculturology and interprets the research of many researchers of different directions regarding this term.